Perumusan Visual Guideline Pada Local Brand La Roux Craft Untuk Meningkatkan Brand Image - Hariyati, Ayu Nur Utami Siwi; Ritonga, Ewy Lady Christin; Prawira, Muhammad Arby; Situmorang, Victoria Via Dolorosa; Pasaribu, Wilson (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
The development and progression in the business field in Indonesia also impacted the people of Medan, resulting in their interest in the growth of local brands, especially fashion local brands. This increased interest is one of the reasons that motivates La Roux Craft as one of the local brands located in Medan to produce handmade designed products. In order to survive, La Roux Craft needs a good branding strategy so it can have a competitive advantage in this era of creative and digital competition. However, La Roux Craft does not yet have a strong branding identity and a sufficient amount of knowledge of digital marketing to navigate its own brand. Based on the situation and the problem that faced by La Roux Craft, this study intends to design a set of brand visual guidelines and do a socialization regarding digital marketing strategy related knowledge to prepare this brand to become a better competitive brand in today’s era. Keywords: brand visual guideline, marketing strategy